Immune reconstruction effectiveness of combination antiretroviral therapy for HIV-1 CRF01_AE cluster 1 and 2 infected individuals. Issue 1 (31st December 2022) - Li, Kang; Chen, Huanhuan; Li, Jianjun; Feng, Yi; Lan, Guanghua; Liang, Shujia; Liu, Meiliang; Rashid, Abdur; Xing, Hui; Shen, Zhiyong; Shao, Yiming
ABSTRACT: There are great disparities of the results in immune reconstruction (IR) of the HIV-1 infected patients during combined antiretroviral therapy (cART), due to both host polymorphisms and viral genetic subtypes. Identifying these factors and elucidating their impact on the IR could help to improve the efficacy. To study the factors influencing the IR, we conducted a 15-year retrospective cohort study of HIV-1 infected individuals under cART. The trend of CD4 + count changes was evaluated by the generalized estimating equations. Cox proportional model and propensity score matching were used to identify variables that affect the possibility of achieving IR. The tropism characteristics of virus were compared using the coreceptor binding model. In addition to baseline CD4 + counts and age implications, CRF01_AE cluster 1 was associated with a poorer probability of achieving IR than infection with cluster 2 (aHR, 1.39; 95%CI, 1.02-1.90) and other subtypes (aHR, 1.83; 95%CI, 1.31-2.56). The mean time from cART initiation to achieve IR was much longer in patients infected by CRF01_AE cluster 1 than other subtypes/sub-clusters ( P  < 0.001). In-depth analysis indicated that a higher proportion of CXCR4 viruses were found in CRF01_AE clusters 1 and 2 ( P  < 0.05), and showed tendency to favour CXCR4 binding to V3 signatures. This study indicated the immune restoration impairment found in patients were associated with HIV-1 CRF01_AE cluster 1, which was attributed to the high proportion of CXCR4-tropic viruses. To improve the effectiveness of cART, more efforts should be made in the early identification of HIV-1 subtype/sub-cluster and monitoring of virus phenotypes.